(untitled) (Clinics, 2009)
OBJECTIVES: To evaluate the effects of intrathecal morphine on pulmonary function, analgesia, and morphine plasma concentrations after cardiac surgery. INTRODUCTION: Lung dysfunction increases morbidity and mortality after cardiac surgery. Regional analgesia may improve pulmonary outcomes by reducing pain, but the occurrence of this benefit remains controversial. METHODS: Forty-two patients were randomized for general anesthesia (control group n=22) or 400 µg of intrathecal morphine followed by general anesthesia (morphine group n=20). Postoperative analgesia was accomplished with an intravenous, patient-controlled morphine pump. Blood gas measurements, forced vital capacity (FVC), forced expiratory volume (FEV), and FVC/FEV ratio were obtained preoperatively, as well as on the first and second postoperative days. Pain at rest, profound inspiration, amount of coughing, morphine solicitation, consumption, and plasma morphine concentration were evaluated for 36 hours postoperatively. Statistical analyses were performed using the repeated measures ANOVA or Mann-Whiney tests (*p